The Impact of Breathing Hypoxic Gas and Oxygen on Pulmonary Hemodynamics in Patients With Pulmonary Hypertension - Carta, Arcangelo F.; Lichtblau, Mona; Berlier, Charlotte; Saxer, Stéphanie; Schneider, Simon R.; Schwarz, Esther I.; Furian, Michael; Bloch, Konrad E.; Ulrich, Silvia (Frontiers in Medicine, 2022)
Background Pure oxygen breathing (hyperoxia) may improve hemodynamics in patients with pulmonary hypertension (PH) and allows to calculate right-to-left shunt fraction (Qs/Qt), whereas breathing normobaric hypoxia may accelerate hypoxic pulmonary vasoconstriction (HPV). This study investigates how hyperoxia and hypoxia affect mean pulmonary artery pressure (mPAP) and pulmonary vascular resistance (PVR) in patients with PH and whether Qs/Qt influences the changes of mPAP and PVR. Study design and Methods Adults with pulmonary arterial or chronic thromboembolic PH (PAH/CTEPH) underwent repetitive hemodynamic and blood gas measurements during right heart catheterization under normoxia (FiO2 0.21), hypoxia (FiO2 0.15) and hyperoxia (FiO2 1.0) for at least 10 minutes Results We included 149 patients (79/70 PAH/CTEPH, 59% women, mean±SD 60±17 years). Multivariable regressions (mean change, confidence interval) showed that hypoxia did not affect mPAP and cardiac index, but increased PVR (0.4 (0.1 to 0.7) WU, p=0.021) due to decreased pulmonary artery wedge pressure (-0.54 (-0.92 to -0.162, p=0.005). Hyperoxia significantly decreased mPAP (4.4 (-5.5 to -3.3) mmHg, p<0.001) and PVR (-0.4 (-0.7 to -0.1) WU, p=0.006) compared to normoxia. Qs/Qt (14±6%) was >10% in 75% of subjects but changes of mPAP and PVR under hyperoxia and hypoxia were independent of Qs/Qt. Conclusion Acute exposure to hypoxia did not relevantly alter pulmonary hemodynamics indicating a blunted HPV-response in PH. In contrast, hyperoxia remarkably reduced mPAP and PVR, indicating a preserved vasodilator response to oxygen and possibly supporting oxygen therapy in patients with PH. A high proportion of PH-patients showed elevated Qs/Qt, which however was not associated with changes in pulmonary hemodynamics in response to changes in FiO2.